RANCANG BANGUN SISTEM INFORMASI GEOGRAFIS SARANA PENDIDIKAN DAN KESEHATAN BERBASIS WEB DI WILAYAH KABUPATEN GUNUNG MAS - Widiatry, Widiatry; Karolita, Devi; Febriliana, Febriliana (Universitas Palangka Raya, 2015)
GIS technology (Geographic Information Systems) is a technology that has the geographicalhighly developed that has the ability to visualize spatial data. Implementing GIS technology is indispensablein the management and use of data in terms of geographic information as a means of mapping a location.In writing this report will discuss about how to build a Geographic Information System (GIS) forweb-based education and health facilities in the district of Gunung Mas on BAPPEDA office. GIS is madeusing the method of UML-Based Web Engineering (UWE) which consists of four steps, namelyRequirements Model (Use Case Model), Content Model (Conceptual Model), Model Navigation andPresentation Model.With the presence of GIS is expected to help facilitate the office BAPPEDA in managinggeographic information regarding education and health facilities in the district of Gunung Mas.